Studi Literatur: Pemanfaatan Media Pembelajaran Digital Berbasis AI Untuk Meningkatan Hasil Belajar IPAS Siswa Sekolah Dasar - Haryani, Putri; Nugroho, Reza Ridho; Arniagsa , Hanyka Anggun; Harsanti , Putri Dewi; Saputra , Idi (Arden Jaya Publisher, 2025)
This study aims to analyze the use of Artificial Intelligence (AI)-based digital learning media in improving Science and Social Studies (IPAS) learning outcomes among elementary school students. Using a literature review method with the PRISMA model, this research identifies, screens, and analyzes 13 relevant articles published between 2015 and 2025. The review shows that AI-based learning media—such as Augmented Reality, Smart E-Comic, Creating App, AI-powered interactive videos, and digital assessment platforms like Quizizz and Wordwall—effectively enhance concept understanding, increase students’ motivation, and foster active engagement through adaptive and interactive learning experiences. AI technology also supports personalized learning by adjusting material difficulty to students’ individual abilities, resulting in improved and equitable learning outcomes. However, challenges remain, including limited digital competence among teachers, inadequate technological facilities, and the need for additional preparation time. Overall, the findings highlight that AI-based digital learning media have significant potential to enhance IPAS learning quality and serve as an innovative approach to meet the demands of 21st-century education.